Airport Runway Capacity and Economic Development: A Panel Data Analysis of Metropolitan Statistical Areas. (August 2013) - Tittle, Derek; McCarthy, Patrick; Xiao, Yuxi
Using an aggregate production function, the impact of runways at commercial airports on several measures of metropolitan statistical areas' economic welfare in combination with labor, private capital, and public-sector capital is estimated. By focusing on runways at commercial airports, we estimate the impact of reducing congestion that sets in and takeoffs and landings as air activity nears the technical limit for safe operations. Both the number of runways and the maximum length of runway available at a given airport correlate positively with real gross metropolitan product with a negative cross product between the two, suggesting a trade-off between the number of flights possible and the size of the aircraft that can use the airport. Additional analysis examines the impact of additional runways on other measures of economic activity.